2022
DOI: 10.1017/pds.2022.189
|View full text |Cite
|
Sign up to set email alerts
|

Automated Requirement Dependency Analysis for Complex Technical Systems

Abstract: Requirements changes are a leading cause for project failures. Due to propagation effects, change management requires dependency analysis. Existing approaches have shortcomings regarding ability to process large requirement sets, availability of required data, differentiation of propagation behavior and consideration of higher order dependencies. This paper introduces a new method for advanced requirement dependency analysis based on machine learning. Evaluation proves applicability and high performance by mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The validity of calculation was tested ex-perimentally and confirmed for requirement sets with 150, 250, 500 and 1,500 requirements. The computation time for each pair of requirements was determined for two representative computing capacities: 16 GB RAM/i7 CPU (regular laptop; Lenovo ThinkPad) and 13 GB RAM/P100 GPU (high-performance cloud server; Google Colab) [75].…”
Section: Success Criterion Sc-2: Processability Of High Number Of Req...mentioning
confidence: 99%
See 3 more Smart Citations
“…The validity of calculation was tested ex-perimentally and confirmed for requirement sets with 150, 250, 500 and 1,500 requirements. The computation time for each pair of requirements was determined for two representative computing capacities: 16 GB RAM/i7 CPU (regular laptop; Lenovo ThinkPad) and 13 GB RAM/P100 GPU (high-performance cloud server; Google Colab) [75].…”
Section: Success Criterion Sc-2: Processability Of High Number Of Req...mentioning
confidence: 99%
“…Due to the limited extent of training data, dependency types are not distinguished by type in order to reduce the number of classes to be differentiated. Since the dataset contains a major class (None) with many entries and a minor class with few entries (Dependent), the criteria needed to be viewed macro averaged (equal weight on all classes) to be significant [75].…”
Section: Success Criterion Sc-14 Sufficient Accuracymentioning
confidence: 99%
See 2 more Smart Citations
“…Machine learning has also been widely applied in cost prediction, software testing and software quality assessment in the software development process, such as in consistency research between developers and tasks [21], integration testing [22], software development cost prediction [23] and software quality assessment [24]. Meanwhile, requirements engineering has also applied a large number of machine learning methods [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], such as requirement acquisition, requirement formalization, requirement classification, the identification of software vulnerabilities from requirement specifications, requirement prioritization, requirement dependency extraction and requirement management. Previous studies have demonstrated that the automatic extraction of requirement dependency relationships is a feasible and effective task [32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%